Measurements of the Electric Field of Zero-Point Optical Phonons in GaAs Quantum Wells Support the Urbach Rule for Zero-Temperature Lifetime Broadening - Bhattacharya, Rupak; Mondal, Richarj; Khatua, Pradip; Rudra, Alok; Kapon, Eli; Malzer, Stefan; Döhler, Gottfried; Pal, Bipul; Bansal, Bhavtosh (Physical Review Letters, 2015)
We study a specific type of lifetime broadening resulting in the well-known exponential "Urbach tail" density of states within the energy gap of an insulator. After establishing the frequency and temperature dependence of the Urbach edge in GaAs quantum wells, we show that the broadening due to the zero-point optical phonons is the fundamental limit to the Urbach slope in high-quality samples. In rough analogy with Welton's heuristic interpretation of the Lamb shift, the zero-temperature contribution to the Urbach slope can be thought of as arising from the electric field of the zero-point longitudinal-optical phonons. The value of this electric field is experimentally measured to be 3 kV cm(-1), in excellent agreement with the theoretical estimate.